Sosialisasi Pengelolaan Limbah Medis Bahan Berbahaya dan Beracun Padat di Fasyankes - Zrimurti Mappau; Miftah Chairani; Fajar Akbar (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Medical waste that is not managed properly will cause the potential for medical was to pollute the environment and transmit disease and can cause work accidents. The purpose of this activity is to socialize medical waste management of hazardous and toxic materials (B3) to health workers in health care facilities. The service method is carried out by conducting counseling on the management of B3 medical waste to 86 health workers, conducting inspections of B3 medical waste containers and placing posters on the dangers of B3 medical waste at each health facility. The activity was carried out in May-October 2022 at the West Sulawesi Province, Binanga Health Center and Rangas Health Center in Mamuju Regency. . The results of the pre and post tests on 86 people filled in so that results were obtained with an average increase in knowledge of 42% with the results of 82 participants increasing knowledge, 3 participants with the same test results and 1 person experiencing a decrease in test results. The results of the activity show that it is important to socialize B3 medical waste management to health workers to prevent potential health hazards. Suggestions for health facilities to pay attention to medical waste containers should be labeled as infectious waste so that they can be easily indentified and medical B3 waste storage areas should be built according to standards set by the government.